A comparative empirical study of Analytic Hierarchy Process and Conjoint analysis: Literature review - Popovic, Milena; Kuzmanović, Marija; Savić, Gordana (Decision Making: Applications in Management and Engineering, 2018)
This paper is based on the main difference between conceptual and theoretical frameworks as well as literature review of comparative studies of two multi-criteria decision making methods: Analytic Hierarchy Process (AHP) and Conjoint analysis. The AHP method represents a formal framework for solving complex multiatributive decision making problems, as well as a systemic procedure for ranking multiple alternatives and/or for selecting the best from a set of available ones. Conjoint analysis is an experimental approach used for measuring individual’s preferences regarding the attributes of a product or a service. It is based on a simple premise that individuals evaluate alternatives, with these alternatives being composed of a combination of attributes whose part-worth utilities are estimated by researchers. Bearing in mind the quality of desired results, it must be dependent on the problems and aspects of research: knowledge of the methods, complexity (number of attributes and their levels), order effects, level of consistency, chooses the appropriate method.